Towards improving participation of students with hearing impairment in leisure and recreational activities for their social adjustment in Nigeria (2019)
Participation of students with hearing impairment in leisure and recreational activities in Nigeria is very low, due to some social and attitudinal factors. This has contributed to their low level of social adjustment. This paper examined improving participation of students with hearing impairment in leisure and recreational activities in Nigeria. The concepts of hearing impairment, leisure and recreational activities, as well as, benefits of leisure and recreational activities to students with hearing impairment, guidelines for improving participation of students with hearing impairment in leisure and recreational activities and barriers to their participation were also examined. Recommendations were given based on the issues raised in the paper.